Studi Kelayakan Pemanfaatan Energi Matahari Sebagai Pembangkit Listrik Tenaga Surya Di Dusun Toalang - Samsurizal Samsurizal; Christiono Christiono; Hendrianto Husada (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2020)
PLTS can be a solution that can be used to provide energy in the area provided far from the electricity network. This study aims to examine the feasibility of PLTS development in. Toalang Hamlet is one of the areas in West Kalimantan that has not been electrified, based on analysis in terms of geographical and demographic areas, has the potential to build PLTS. So to examine the feasibility of PLTS development the factors were collected and analyzed using PVSyst software. Of the several factors studied from the average air temperature between 21.0 to 35.4 degrees Celsius and the average humidity between 80% to 90%. Maximum irradiation at 11.00 a.m. and reached a value of 386 kWh / m2, and effective irradiation at the same time reached a value of 362 kWh / m2. The potential data of solar energy obtained from the measurement results with a pyranometer is 680 Watt / m2 at 10:05 WIB using a solar meter measuring instrument. From the results of calculations and analysis using PVSyst software, what is concluded is; PLTS built in the area Centralized PLTS with Off Grid system which has a capacity of 21.84 kWp, load 55.758 Wh / day and Direction of solar panels to the south with a slope angle of 4 (four) degrees. Keywords: Feasibility Study, Renewable Energy, PLTS, PVsyst